Developmental anatomy and apical organization of the primary root of cork oak (Quercus auber L. - Verdaguer, Dolors; Molinas, Marisa (International Journal of Plant Sciences, 1999)
Using histological techniques, we investigated the development and organization of the primary root and the root apex of Quercus suber L. (cork oak), a Mediterranean woody species growing in semiarid conditions. The presence of a quiescent center was also investigated. The histogenesis of the vascular system begins with the maturation of the protophloem elements. Primary phloem and xylem strands form alternately, and maturation proceeds centripetally, although xylem differentiation does not reach the center of the root, which is occupied by a pith. Most protoxylem elements were fully mature well before the endodermis entered State I with the formation of the Casparian strip. A continuous vascular cambium forms before the initiation of the phellogen in the outermost pericyclic layer. In the primary root the apex has an open organization with four groups of initials: vascular cylinder initials, cortical initials, lateral root-cap initials, and columella initials. The quiescent center includes the vascular initials and some derivatives. These features contrast with the radicle in mature and germinating embryos that have a closed organization with three groups of initials and a wider quiescent center.
Keywords: development; meristem; primary root; Quercus suber; quiescent center; vascular development

Stress proteins co-expressed in suberized and lignified cells and in apical meristems - Pla, Maria; Huguet, Gemma; Verdaguer, Dolors; Puigderrajols, Pere; Llompart, Blanca; Nadal, Anna; Molinas, Marisa (Plant Science, 1998)
We report the cloning of a small heat shock protein, Qs –HSP17, and an osmotin like protein, Qs –OLP, from cork oak phellem tissue (cork cells). Both genes are expressed in suberizing cells and in other cells subject to endogenous stress associated with free radicals. We provide evidence that smHSPs and OLPs accumulate in overwintering buds and speculate that their role is similar to that in seed dormancy. We also show that both stress proteins are mainly located in the region of the quiescent center in root apex and in central meristem in the shoot apex. We emphasize that smHSPs and OLPs are expressed in cells growing under endogenous stress or facing long life-span. We discuss a possible role of these stress proteins against oxidative stress
Keywords: cork-oak; osmotin like proteins; phellem; Quercus suber; small heat shock proteins; tissue specificity

Development and ultrastructure of the endodermis in the primary root of cork oak (Quercus suber) - Verdaguer, Dolors; Molinas, Marisa (Canadian Journal of Botany, 1997)
The endodermis maturation process was studied in the primary root of the cork oak (Quercus suber L.) with emphasis on the chemical nature of the cell wall and on the possible role of tannins. Tannins were found in endodermal and adjacent cortical cells in all maturation stages. We discuss our findings in relation to the previous literature in other woody and herbaceous species. The results of the histochemical tests showed differences in the aliphatic compounds of the suberin between the Casparian strip suberin and the suberin layer deposited in state II cells. Plasmodesmata were present in radial and tangential walls during the entire maturation process. The significance of plasmodesmata and of the suberin deposition pattern is discussed in relation to apoplastic and symplastic transport in roots. Key words: Casparian strip, endodermis, primary root, suberin, Quercus suber L.
doi: 10.1139/b97-087
Keywords: Casparian strip; endoderrnis; primary root; Quercus suber L.; suberin